Self-authenticating identifiers. - Cerf, Vinton G. (Communications of the ACM, 2018)
This article discusses the use of public key cryptography in the encryption and decryption of data. The author comments on the role of self-authenticating identifiers in the process of encryption and decryption and examines the creation of certificate authorities to link these identifiers to public keys.